The cost of exploitative leadership: how self-control depletion and organizational support shape employee outcomes - Zhang, Xueqin; Wang, Zerui; Jiang, Xiyuan; Xu, Fei (Frontiers in Psychology, 2025)
IntroductionExploitative leadership, regarded as a manifestation of dark leadership, has recently attracted heightened academic interest because of its harmful consequences for employees. However, existing research has paid relatively little attention to the ways in which such leadership shapes critical employee outcomes, including intentions to leave and procrastination at work. Framed within conservation of resources theory, this study probes the latent pathways through which exploitative leadership erodes employee resources, precipitating both turnover intentions and procrastinatory conduct, while highlighting contextual levers that might temper these deleterious effects.MethodsTo test the proposed hypotheses, we collected two-wave matched data from 296 full-time employees across various industries. Hierarchical regression and bootstrapping analyses were employed to assess the mediation and moderation effects.ResultsThe results unveiled that exploitative leadership precipitates heightened turnover intentions and procrastinatory behavior among employees, with self-control depletion operating as a pivotal mediator. Crucially, perceived organizational support functioned as a buffering mechanism, dampening both the impact of exploitative leadership on self-control depletion and its downstream indirect effects on turnover intention and workplace procrastination.DiscussionThis study contributes to the growing literature on exploitative leadership and its consequences for employee attitudes and behaviors. It extends our understanding of the interactive effects between exploitative leadership and organizational support, and uncovers the critical role of self-control resources in shaping employees’ withdrawal responses. Practical implications for organizational leaders are also discussed.